Zanubrutinib plus R-CHOP improves the treatment effect of newly diagnosed diffuse large B cell lymphoma with double expression of MYC and BCL-2 - Zhang, Min; Wu, Yingying; Cheng, Zhipeng; Zhang, Lu; Liu, Lin; Liu, Fang; Cui, Guohui; Xia, Linghui; Hu, Yu; Mei, Heng; Guo, Tao; Fang, Jun (Frontiers in Immunology, 2025)
BackgroundRelevant studies have demonstrated the poor treatment outcomes and prognosis for double-expressor diffuse large B cell lymphoma (DE-DLBCL) in the rituximab era. Zanubrutinib plus R-CHOP (rituximab, cyclophosphamide, doxorubicin/liposomal doxorubicin, vincristine, prednisone; ZR-CHOP) has shown efficacy in untreated non-GCB DLBCL patients with extranodal involvement. However, its efficacy in newly diagnosed DE-DLBCL remains uncertain.ObjectiveThis retrospective study sought to assess the efficacy and safety of ZR-CHOP in comparison to R-CHOP in treatment-naïve patients with DE-DLBCL.MethodThis study assessed 78 patients with newly diagnosed DE-DLBCL who were admitted between June 2017 and January 2024. Among them, 55 patients received the R-CHOP regimen, while 23 patients were treated with the ZR-CHOP regimen. The clinical characteristics were well balanced between the two groups.ResultsThe complete response rates (CRR) were higher in the ZR-CHOP group than the R-CHOP group, regardless of whether patients completed 4 or 6 treatment cycles (P= 0.019; P= 0.025). ORR in the ZR-CHOP group showed a higher trend than that in the R-CHOP group (P= 0.624; P= 0.219). The median follow-up period was 23.3 months, and the predicted median progression free survival (PFS) in the R-CHOP group was 22.8 months, whereas the median PFS in the ZR-CHOP group was not reached. The 1-, 2-, and 3-year PFS rates in the ZR-CHOP group showed a beneficial trend compared with the R-CHOP group, but there was no statistical difference (P= 0.072). However, the PFS of the ZR-CHOP group was longer than that of the R-CHOP group in patients with Ki67 index >75% (P= 0.034) and p53 expression >50% (P= 0.0033). The predicted median overall survival (OS) in the ZR-CHOP and R-CHOP groups were not reached. The 1-, 2- and 3-year OS rates were not significantly different between the two groups (P= 0.29). The most common adverse event in both groups was hematotoxicity, but there was no significant difference in the incidence of all adverse events between the two groups.ConclusionFirst-line treatment with the ZR-CHOP regimen improved CRR in the untreated patients with DE-DLBCL and prolonged PFS in the Ki67 index >75% subgroup and the p53 expression >50% subgroup.